Ownership structure and corporate performance of Chinese listed companies - HUANG, YIHAN (2017)
This paper investigates the relationship between the performance of listed Chinese companies and their ownership structure. This article analyses all of the non-financial companies, including 12 industries. These companies are listed on the Shanghai Stock Exchange (SHSE) and the Shenzhen Stock Exchange (SZSE) from 2012 to 2016. This study indicates that the state-owned shareholding is negatively related to corporate performance. There is a positive relationship between legal person shares and the proportion of institutional investors, but the opposite direction changes with the percentage of tradable share. The findings suggest that ownership structure affect the performance of listed companies. This paper finds that ownership concentration has an important influence on the performance of companies, and the characteristic of the large shareholders is also a significant determinant.